Between Austinâ€™s Speech Acts and Performative Utterances - Onwuegbusi, Martin Okwu (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
This paper is an attempt to delineate Austinâ€™s theory of speech acts which specifies the conditions, under which certain speeches can constitute â€˜speech actâ€™.  The theory of speech acts constitutes what J.L. Austin puts forward in his work â€œHow to do things with Wordsâ€, detailing the conditions that must be met for a given speech act to be performed felicitously.  In this case, failures of felicity may lead to: misfires or abuses; which may be because, the person uttering such a felicitous speech lacks the authority to do so or he is an imposter. Austin later came up with a more general theory of speech acts, which include Locutionary, Illocutionary and Perlocutionary Acts.